Associations of eating and drinking habits with cardiovascular disease and diabetes in the adult population: data from the ESSE-RF epidemiological study - N. S. Karamnova; A. I. Rytova; O. B. Shvabskaya; Yu. K. Makarova; S. A. Maksimov; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2021)
The presence of a disease, the prognosis of which can be improved by dietary modification, motivates a patient to change their eating habits.Aim. To study the associations of dietary patterns and alcohol consumption with cardiovascular diseases (CVDs), diabetes, myocardial infarction (MI), and stroke in the adult population.Material and methods. The analysis was carried out using data from representative samples of population from 13 Russian regions aged 2564 years (n=19520; men, 7329; women, 12191). The response rate was ~80%. Dietary characteristics were assessed by frequency method.Results. In the diet of people with CVDs, the daily intake of vegetables/ fruits increases by 84% in men and by 19% in women, while the use of animal fats in cooking decreases by 28% and 20%m respectively (p<0,0001). Women with CVDs reduce the consumption of processed meat and sweets by 16 and 19%, respectively (p<0,005). Persons with prior MI reduce the consumption of sweets in the diet: men by 38% and women by 30%. Men with prior MI have higher daily consumption of cereals by 31%, vegetables and fruits by 46%, low-fat dairy products — 2,4 times. In addition, they are more adherent to a healthy and cardioprotective diet by 3,65 and 1,75 times, respectively. Dietary changes in those with prior stroke were noted only in women in the form of a 29% decrease in excess salt intake (p=0,0075). In the diet of people with diabetes, there is decreased consumption of sweets and an increased intake of vegetables/fruits: by 77 and 69% in men and by 79 and 69% in women, respectively (p<0,0001). Men with diabetes are 3 times more likely to adhere to a healthy diet, and women — 2,3 times (p=0,0039 and p<0,0001, respectively).Conclusion. Patients with CVDs, MI, and diabetes have a healthier diet than healthy persons.